Thickness of the ligamentum flavum: correlation with age, sex, side, spinal level and degenerative disc disease - Agrawal, Basudev; Sao, Alok; Agrawal, Garima (International Journal of Research in Medical Sciences, 2025)
Background: Few researchers have studied thickness at different spinal levels and compared with age, sex, side, spinal level and relationship with degenerative disc disease. However, there is no literature pertaining to the study of LF thickness correlation with all these five parameters in single study. Here, we determined the correlation of dorsal and lumbar spine LF thickness with age, sex, side asymmetry, at different spinal levels and relation with degenerative disc disease (DDD) using magnetic resonance imaging (MRI). Methods: LF thickness was measured retrospectively at all dorsal and lumbar spinal levels (T1 to S1 level) on both sides in MRI scans of 200 individuals attending Shree Narayana Hospital, Raipur, Chhattisgarh from 1st July 2023 to 30th June 2024. On axial T2-weighted MRI at the mid-disc level, LF thickness was measured perpendicular to the lamina border, either at half the length of LF or at maximum thickness, whichever was greater. Results: All results were collected in tabular form. All individuals were divided into three age groups- 21to 40 years,41 to 60 years, 61 to 80 years. LF thickness increase significantly with increasing age, but there was no side or sex dominance. LF thickening has a predominant tendency to occur specifically at the T10-T11 and L4-L5 levels and was significantly more in those having associated degenerative disc disease. Conclusions: LF thickness does not appear to have any side or sex dominance but increase significantly with increasing age. Also, LF thickness have significant correlation with spinal levels. LF thickness was significantly higher in those having associated degenerative disc disease.